If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 3) + -8x = 36 Reorder the terms: 6(3 + x) + -8x = 36 (3 * 6 + x * 6) + -8x = 36 (18 + 6x) + -8x = 36 Combine like terms: 6x + -8x = -2x 18 + -2x = 36 Solving 18 + -2x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -2x = 36 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 36 + -18 -2x = 36 + -18 Combine like terms: 36 + -18 = 18 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| 4(8k+5)= | | (3x-5)(2x+8)= | | (x+3)(x+3)=X^2+81 | | 456=(20+2x)(15+2x) | | 1+4(x-8)=4-5(x-1) | | x^2+y^2-6x+4y+6=0 | | 8n+14=2n-4 | | 9x+3y=167 | | 5(5+x)+10=5-5x | | 3x-10+x+14=160 | | 2x-1+6=11 | | 7y^2+4y= | | 6m+4(6m-4)=26-8(2m-12) | | 3x+6y=168 | | 2(x+7)-5(2x-6)=92 | | 12x^2+4x=-5 | | p+4p=15 | | 1=-16x^2+b | | 9x+6y=171 | | 4cos^2(x)=5-4sinx | | 9x+6y=170 | | x*20=2 | | 18=-16t^2+80t+18 | | log(4x+1)=log(25) | | (cozx-1)(cosx-2)=0 | | 3x^2+24x+3=0 | | 1+0.80a=2+0.75a | | 2(4x-9)=42 | | 5x=4+2y | | 0.05(7-x)+0.1x=0.56 | | log(6)(5x+4)=2 | | 6a^2-6a=0 |